AHMAD SADALI Al Quran dalam Pribadi Seniman Islami - Amir Hamzah (Ars: Jurnal Seni Rupa dan Desain, 2007)
Islam in society nowadays has evolved over a very long lime, especially as the span of time betweenthe messenger, the Prophet Muhammad, becomes more distant. This religion which reaches the disciples'heart faces many, various considerations. One o f these considerations which is mostly accepted by thesociety is secularity towards the religion. Religion is considered to be the other side o f a person's life, whichis not supposed to be involved in societal matters. Hoioever, at the same time, a phenomenon of "back tosyariah (Islamic law)" becomes apparent in Moslem society. A proportion o f Islamic disciples rediscover aconnection and realise its jwtential in ruling human life. I he Koran becomes a solution in confronting thislife.It affects not only common people's thoughts but also artists in creating artworks. Vie late AhmadSadali was a Moslem artist who realized this potential in his life. He tried to identify himself as "idilalbab", a human being exemplified by his Cod, as written in the Holy Book in which he believed. This factor,eventually, differentiates his personality as well as the artworks he produced from his fellow artists andtheir oion works.Keywords: Ahmad Sadali, Islamic identity, The Koran, verse